Multiobjective fractional programming problems and the sufficient condition involving Hb – (p, r)-η- invex function - Gao, Xiaoyan; Niu, Huan (MATEC web of conferences, 2021)
On the basis of arcwise connected convex functions and (p, r) −η - invex functions, we established Hb –(p, r) –η- invex functions. Based on the generalized invex assumption of new functions, the solutions of a class of multiobjective fractional programming problems are studied, and the sufficient optimality condition for the feasible solutions of multiobjective fractional programming problems to be efficient solutions are established and proved.